The Role of Archiving Applications and Digital Literacy in Advancing Electronic-Based Government System Readiness: Insights from Indonesia - Chairul Huda Atma Dirgatama; Arinta Kusumawardhani; Irsyadul Ibad; Rony Kurniawan Pratama; Arif Wahyu Wirawan; Cheryl Marlitta Stefia; Maminirina Fenitra Rakotoarisoa (Record and Library Journal, 2026)
Background of the study: Indonesia's Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik, SPBE) requires municipalities to establish robust digital infrastructure while simultaneously ensuring that citizens possess the competencies necessary to access and utilize public digital services effectively. Purpose: This study investigates whether the quality of archiving applications and the level of digital literacy affect SPBE readiness in Surakarta City, both jointly and separately, and determines which factor exerts the stronger influence. Method: A quantitative survey was administered to 100 respondents proportionally selected from Surakarta’s five sub-districts using the Slovin formula and proportional random sampling. The hypotheses were examined through multiple linear regression analysis using SPSS version 25. Findings: The findings demonstrate that both archiving applications and digital literacy have positive and statistically significant effects on SPBE readiness, with archiving applications exhibiting the stronger effect within this sample. Conclusion: These results suggest that municipal SPBE readiness depends not only on citizens’ digital competence but also on the quality of internal administrative digital systems.